Dynamic Responses of the Caudal Neurosecretory System (CNSS) Under Thermal Stress in Olive Flounder (Paralichthys olivaceus) - Yuan, Mingzhe; Li, Xiaoxue; Long, Tianyi; Chen, Yan; Lu, Weiqun (Frontiers in Physiology, 2020)
Temperature is a critical environmental factor that affect most biological and physiological processes in fish. The caudal neurosecretory system (CNSS) is unique to fish and is proved to maintain homeostasis during seasonal alterations. However, the dynamic expression and secretion pattern of its major hormones, corticotrophin-releasing hormone (CRH), urotensin I (UI) and urotensin II (UII), and their response to thermal stress has not been studied. CRH, UII and cortisol in plasma, gene expression levels of CRH, UI and UII in the CNSS of olive flounder (Paralichthys olivaceus) was therefore characterized. UI- and UII- positive Dahlgren cells, as well as cell proliferation in the CNSS, was also quantified. The results showed that plasma cortisol and CRH were increased in both low temperature (LT) and high temperature (HT) groups. However, there was no difference in plasma UI and UII during thermal stress. In CNSS, CRH, UI and UII mRNA levels were all significantly elevated in response to acute hypothermal stress and recovered back to the control (normal) level after 8 days of adaptation. During hyperthermal challenge, gene expression of CRH and UI only significantly increased after 8-days of transfer but no change in UII was observed. We also demonstrated an increasing percent of UI-positive Dahlgren cells in the CNSS of 8-days hyperthermal stressed fish. However, no BrdU-labelled Dahlgren cells were found among the three treatment groups. Collectively, our results demonstrate that the CNSS is subject to dynamic responses under thermal stress and expands upon the the role of the CNSS in thermoregulation. The dynamic responses of hormone levels and the gene expression of CRH, UI and UII in CNSS are all involved in the process of hyper- or hypo-thermal stress and adaptation.